DYNAMICS OF STUDENTS’ REPRESENTATIONS ABOUT PHYSICAL CULTURE AS AN ACADEMIC DISCIPLINE AND LIFESTYLE - Narkhov, D.Yu.; Dobrynin, I.M.; Narkhova, E.N. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to evaluate changes in the students’ perception of physical culture in the context of value orientations. Methods and structure of the study. The results of two waves of a mass questionnaire survey of students in 2015 and 2022 were compared. The number of respondents included students involved in physical education both as part of an academic discipline and independently. Results and conclusions. A decrease in the gap between the verbal statements of attitudes towards a healthy lifestyle and the real valeological behavior of students against the background of changes in value attitudes was found. The conclusion is made about the shift of physical culture from terminal to instrumental value, the possibility of involving non-traditional healthy lifestyle methods and youth subcultural sports in the educational process as an additional driver of sports.